2022
DOI: 10.3390/f13071128
|View full text |Cite
|
Sign up to set email alerts
|

Heritage Trees as an Important Sanctuary for Saproxylic Beetles in the Central European Landscape: A Case Study from Litovelské Pomoraví, Czech Republic

Abstract: Intensive forest and agroforestry management has greatly reduced the biodiversity of saproxylic organisms. Large trees are one of the most important refuges of saproxylic beetles. These large trees that grow outside and inside the forest are declining in the wider landscape. Heritage trees are one of the essential groups of beneficial trees in the landscape. We investigated saproxylic beetles associated with 35 selected oak heritage trees in Litovelské Pomoraví in the eastern Czech Republic. The study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…Our results are generally consistent with those of Wermelinger et al (2007), Seibold et al (2016), Vogel et al (2020) and Oto et al (2022). These studies showed high affiliation between Coleoptera and open space, forest edges and/or sunlight.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are generally consistent with those of Wermelinger et al (2007), Seibold et al (2016), Vogel et al (2020) and Oto et al (2022). These studies showed high affiliation between Coleoptera and open space, forest edges and/or sunlight.…”
Section: Discussionsupporting
confidence: 93%
“…Plots at higher elevations had lower levels of basal area and were more open (Table 2). While the mechanisms driving higher abundance at higher elevations do not necessarily include the higher levels of open space at higher elevations, the affiliation of saproxylic Coleoptera to both open space and edge habitat is supported by other studies (Oto et al, 2022; Seibold et al, 2016; Wermelinger et al, 2007). Open space and edge habitat can be a proxy for sunlight, and higher amounts of sunlight‐exposed substrate are known to be important predictors of saproxylic biodiversity (Jonsell et al, 1998; Lindhe & Lindelöw, 2004; Thorn et al, 2016; Vogel et al, 2020).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A higher number of species was recorded in sunny plots, which implies that beetles prefer sunny habitats ( e.g. , Lettenmaier et al, 2022 ; Nakládal et al, 2022 ). Beer and wine consistently captured higher numbers of beetle species than vinegar and water in sunny plots.…”
Section: Discussionmentioning
confidence: 98%
“…Besides aqueous solutions with different preservatives, fermenting (attractive) liquids are also used to study beetle communities ( Ruchin, Egorov & Khapugin, 2023 ). Some studies have used beer, wine, and vinegar as trapping fluids to assess beetle biodiversity in relation to surrounding environmental conditions ( Ruchin & Egorov, 2021 ; Nakládal et al, 2022 ; Spina et al, 2023 ) or to monitor target groups, e.g. , stag beetle (Lucanidae) ( Bardiani et al, 2017 ), flower chafer (Scarabaeidae: Cetoniinae), longhorn beetle (Cerambycidae) ( Touroult & Witté, 2020 ) or social wasps (Hymenoptera: Vespidae) ( Dvořák & Landolt, 2006 ).…”
Section: Introductionmentioning
confidence: 99%